EFEKTIVITAS EXPRESSIVE WRITING THERAPY DALAM MENURUNKAN TINGKAT STRESS PADA REMAJA DENGAN ALBINO DITINJAU DARI TIPE KEPRIBADIAN INTROVERT DAN EKSTROVERT - Aulia Maharani, Shanaz Nadia; Noviekayati, IGAA; Meiyuntariningsih, Tatik (Persona:Jurnal Psikologi Indonesia, 2017)
Abstract                                The purpose of this study was to investigate the effectiveness of expressive writing therapy in reducing stress levels in adolescents with albinism, and to see the difference in the effects of expressive writing therapy to reduce stress in adolescence with albinism in terms of introverted personality types and. This study included experimental research with Quasi Experiment with one group pretest-posttest design. Subjects used in this study were 6 (six) adolescents with albinism, 3 (three) subjects with introverted personality type and 3 (three) subjects with extrovert personality type. The six subjects were selected for having a high stress score. The instrument used is a stress scale developed from the Lazarus theory with reliability of 0.948 and the scale of personality types developed from Eysenck theory with reliability and validity of 0.720. The results showed expressive writing therapy method is effective to reduce stress in adolescents with albinism. The results also showed no difference in stress reduction between subjects with introverted personality and subjects with extroverted personality.Keywords: Expressive Writing Therapy, Stress, Introvert, Extrovert